Effects of Ethrel, packaging and waxing on degreening, quality and shelf life of sweet oranges - Elkashif, Mohamed; Abdelsadik, Hilana; Elamin, O. M. (Gezira Journal of Agricultural Science, 2015)
Post harvest handling practices of sweet oranges are very poor in the Sudan and result in great losses. Oranges grown in central Sudan reach the ripe stage while they are still green in colour. The lack of orange colour development is due to the relatively high temperatures in this region. Therefore, the objective of this research was to find out the effects of Ethrel, packaging and waxing on sweet orange degreening, quality and shelf life. Experiments were conducted at the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during the seasons of 2013-2014. Ripe, green oranges were treated with Ethrel at two concentrations: 1ml/l, 2ml/l or left untreated as a control. Packaging treatments consisted of wrapping oranges in intact or perforated polyethylene film, waxed or left unpackaged as control. Treatments were arranged in a completely randomized design with two replicates. Results showed that treatment of oranges with Ethrel at both concentrations significantly resulted in degreening of oranges and development of a uniform orange colour as compared to the control. Oranges packaged in intact polyethylene film or waxed recorded the minimum weight loss followed by those wrapped in perforated film, whereas the highest weight loss was recorded for the unpackaged and unwaxed oranges. Also, packaging in intact film or waxing of oranges resulted in the longest shelf life compared to the other treatments. Total soluble solids and vitamin C contents were highest in oranges packaged in intact film or waxed, whereas the least contents were recorded for the control. Ethrel treatment had no significant adverse effects on orange chemical composition. It is recommended to degreen oranges using Ethrel at 2ml/l and package them in intact polymeric film or coat them with wax.   معاملات ما بعد الحصاد للبرتقال في السودان غير متطورة وينتج عنها خسائر كبيرة. يصل البرتقال المنتج في أواسط السودان إلى طور النضج وهو أخضر اللون. يعزى عدم تلوين البرتقال إلى ارتفاع درجات الحرارة في هذه المنطقة.  الهدف من هذه الدراسة هو معرفة أثر مادة الأثرل على تلوين البرتقال وتأثير التغليف والتشميع على جودة وفترة صلاحية البرتقال. أجريت التجارب في كلية العلوم الزراعية، جامعة الجزيرة واد مدني السودان خلال موسمي 2013-2014م. تمت معاملة ثمار البرتقال الأخضر بمادة الأثرل 1 و 2 ملم/لتر أو ترك كشاهد. معاملات التغليف اشتملت على تغليف البرتقال في أكياس البولي إيثلين السليمة أو المخرمة أو التشميع أو بدون تغليف كشاهد. صممت التجارب نسق التصميم العشوائي الكامل بمكررين. أوضحت النتائج أن معاملة البرتقال بمادة الأثرل أدت إلى زوال اللون الأخضر وتلوين البرتقال بلون برتقالي جميل بالمقارنة مع الشاهد. تغليف البرتقال في أكياس البولي إثيلين السليمة أو تشميعه أدى إلى أدنى فقدان الوزن، يليه التغليف في أكياس مخرمة، بينما كان أعلى فقدان الوزن في الشاهد. محتوى المواد الصلبة الذائبة وفيتامين "ج" كان أعلى في البرتقال الذي تم تغليفه في أكياس البولي إيثلين السليمة أو التشميع، بينما كان أدنى محتوى في الشاهد. معاملة البرتقال بمادة الأثرل لم يكن لها أي تأثير ضار على التركيب الكيميائي للبرتقال. لذلك يوصي بمعاملة البرتقال الأخضر بمادة الأثرل لتلوينه وتغليف الثمار في أكياس البولي إيثلين السلمية أو التشميع للحفاظ على الجودة وزيادة فترة الصلاحية أو العمر التخزينية للبرتقال.